Histórias de vida de professoras que desenvolvem práticas docentes multiculturais - Fontenele, Cristiane Ferreira (Universidade Federal de São Carlos, 2008)
In this work, I analyze the life story and education of four elementary school teachers, working in cycle I (Grade 1 to 4) of the São Carlos Municipal education system, selected because of their implementation of inter-multicultural teaching. To substantiate my theory, I researched studies related to life story, teaching graduation and inter-multicultural perspective in education. This work clarified and generated new knowledge in: life and educational background that contributed to the inter-multicultural initiative; the reasons behind this choice of work-orientation; their personal and professional characteristics; their continuous search for change and innovation inside their present school organization system and the difficulties found and the opportunities created by them during their work development. The analyzed results show the progress of the teachers towards the development in the inter-multicultural educational practices in many moments of their life and careers. The four teachers via life experience, formal education and practical work acquired and developed knowledge and approaches that influenced their pedagogic work towards the inter-multicultural education ideas. The result of this learning in their work, could have been noticed when it started to guide the choice of new teaching contents, adoption of news procedures and in the establishment of new relationships at school and in the classroom. I believe that understanding how the teachers were constituted as professionals that apply intermulticultural teaching practices, it will be possible to think about models and teaching application in teachers more adequate to reach hearts and minds.
Keywords: Educação intercultural; História de vida; Professores - formação; Educação Intermulticultural; Inter-multicultural education; Life story; Teachers training; CIENCIAS HUMANAS::EDUCACAO